Mapping the history of Malaysian theatre: an interview with Ghulam-Sarwar Yousof - Ramlan , Madiha; Quayum, Mohammad Abdul (IIUM, 2010)
An interview article that deals with the different aspects as well as the history of Malaysian theatre.